Modelling consumer's behaviour towards adoption and sustainable usage of parcel lockers - Lim, Jun Wei (Nanyang Technological University, 2024)
In recent years, in the realm of logistic operations where last-mile delivery plays the pivotal role in influencing transportation efficiency, it faces significant challenges in maintaining operational effectiveness, primarily due to the escalating demands in last-mile urban logistics. In view of this last mile urban logistics issue, there has been much effort to alleviate it with innovative solution by way of parcel lockers (PL), yet the problem still remains unsolved due to the low adoption rates of PL, thereby prompting the need for further intervention strategies. Hence, this study which anchors on the often-overlooked irrational psychological factors influencing consumer behaviour aims to provide relevant intervention solutions required to address the low adoption rate of PL. By analysing the different characteristics associated with the irrational psychological aspect of adoption intention through conducting a survey across 800 consumers, within the context of Singapore. It was identified and concluded through the results that confirmation bias, status quo bias and transition cost exhibited relative insignificant correlation to the adoption intention of PL. Whereas transition benefits and habit were deduced to have the most positive and most negative correlation to consumers' intention to embrace PL services respectively. Furthermore, transition cost was also concluded to possess a negative correlation to self-efficacy of consumers intention but unlike transition benefit, it displayed a weak positive correlation to social norm. Thereafter, the study also went on to propose several managerial interventions to improve consumers’ intention to adopt PL by introducing the provision of free trials for non-users and tailored guidance for new users in view of helping them take the first step into transiting and easing into the adoption of PL. Additionally, this study also identified and emphasised on the great importance of tailoring transition benefits to suit consumers’ needs in view of conferring a clear advantage over other last-mile delivery methods to improve adoption intention of PL. This study has provided valuable insights and coverage on literature regarding the irrational psychological aspect of PL adoption intention as well as managerial interventions to improve the adoption rate of PL for the last-mile delivery.